Correlación entre el índice de carga puntual y el número de rebote del Martillo Schmidt para la arenisca de la antigua cantera de Servita (2017)
In this Final Master's Work a Correlation between the Point Load Index and the Schmidt Hammer Rebound Number is presented, tests performed on the slope formed by Sandstone of the old Quarry of Servita, aiming to improve the times of obtaining parameters Of design, and in the most reliable way taking advantage of the materials we have in each work area, as in this case the sandstones of the Labor Stone. Knowing the resistance to deformation that a rock has, it is possible to predict the behavior of the material in different natural and anthropic scenarios, such as landslides or construction of buildings.